Features of the formation of attitudes towards the disease in patients (PROBLEMS AND SOLUTIONS OF SCIENTIFIC AND INNOVATIVE RESEARCH, 2025)
The purpose of this article is to reveal specific psychological and psychosomatic changes in patients with tuberculosis and the factors that affect them. The factors influencing the formation of patient’s loyalty to treatment,  the patient’s personality and the mechanism of psychological influence during psycho-preventive work with the patient are analyzed.